Internet Marketing and Consumer Purchase Decision: A Case Study of Jumia Uganda - Noah Emodit (Uganda Christian University, 2023)
This study assessed the influence of internet marketing on consumer purchase decision in Jumia Uganda. Specifically the study was guided by the following objectives: to establish the effect of social media marketing on consumer purchase decision in Jumia Uganda: to determine the influence of website marketing on consumer purchase decision in Jumia Uganda and to establish email marketing on consumer purchase decision in Jumia Uganda. The study predominantly employed qualitative and questionnaire approach, a sample size of 217 was selected where a response rate of 96 percentages were obtained, 12 interview guides and a documentation review checklist were used to collect data samples of respondents. Data was analysed by use of both qualitative and quantitative analysis techniques. Data analysis involved use of both descriptive and inferential statistics such as; mean, standard deviation, percentage, correlation coefficient and regression analysis. Findings show that there was a positive correlation (r=.26.6) between social media marketing and consumer purchase decision in Jumia Uganda. Thus social media marketing accounted for 26.6% change in consumer purchase decision in Jumia Uganda. Findings also showed that there was a positive correlation (r=.042) between website marketing and consumer purchase decision in Jumia Uganda. Thus website marketing accounted for 42% change in consumer purchase decision in Jumia Uganda. Lastly, findings revealed that there was a positive correlation (r=.66.2) between e-mail marketing and consumer purchase decision in Jumia Uganda. Thus e-mail marketing accounted for 66.2% change in consumer purchase decision in Jumia Uganda. It was concluded that Jumia Uganda observes internet marketing activities such as online visitor, display adverts sharing of content, optimised search engine optimization, e-mail campaigns so as to affect consumer purchase decision. It is thus recommended that there is need for Jumia Uganda to ensure that internet marketing activities offer information satisfaction since it affects the quality of goods that are offered hence need to improve the quality of service. Furthermore, online shopping pages should offer immerse choice, data servicing, steadfastness and item examination considering developing trust online is complicated than the normal outlets. Lastly, consumer with internet experience should be in position to embrace and utilize online information due to the high confidence likely influenced by online reviews which impact consumer purchase decision.
This is a dissertation.